Magnetically Triggered Monodispersed Nanocomposite Fabricated by Microfluidic Approach for Drug Delivery - O. Yassine; E. Q. Li; A. Alfadhel; A. Zaher; M. Kavaldzhiev; S. T. Thoroddsen; J. Kosel (International Journal of Polymer Science)
Responsive microgel poly(N-isopropylacrylamide) or PNIPAM is a gel that can swell or shrink in response to external stimuli (temperature, pH, etc.). In this work, a nanocomposite gel is developed consisting of PNIPAM and magnetic iron oxide nanobeads for controlled release of liquids (like drugs) upon exposure to an alternating magnetic field. Microparticles of the nanocomposite are fabricated efficiently with a monodisperse size distribution and a diameter ranging from 20 to 500 µm at a rate of up to 1 kHz using a simple and inexpensive microfluidic system. The nanocomposite is heated through magnetic losses, which is exploited for a remotely stimulated liquid release. The efficiency of the microparticles for controlled drug release applications is tested with a solution of Rhodamine B as a liquid drug model. In continuous and pulsatile mode, a release of 7% and 80% was achieved, respectively. Compared to external thermal actuation that heats the entire surrounding or embedded heaters that need complex fabrication steps, the magnetic actuation provides localized heating and is easy to implement with our microfluidic fabrication method.